Beating structure on the spectrally resolved four-wave mixing: polarization dependence - , Suryadi; Ishihara, Teruya; Kadoya, Yutaka; Yamanishi, Masamichi (The Physical Society of Japan, 2000)
We have performed spectrally resolved four-wave mixing measurements on inhomogeneously broadened GaAs/AlAs quantum-well structures. Under crosslinear polarization we observed a beating structure as a function of the delay time at higher energy region of the emission band with period of 0.95 ps. The beating was constructive at delaytime τ = 0 ps. This behavior results from the interference between two biexciton intermediate states with different energies coupled to a common one-exciton state, as we show by a comparison with analytical model calculation of the double Feynman diagrams of the same type.